Devising a method for controlling articles during photopolymer 3D printing - Nikitin, Dmytro; Nevliudov, Igor; Zharikova, Iryna; Bronnikov, Artem; Strelets, Roman (Eastern-European Journal of Enterprise Technologies, 2025)
This study’s object is those factors that affect the defects of photopolymer 3D models. The task addressed relates to identifying the factors that cause the appearance of surface defects and deviations in geometric dimensions in photopolymer 3D models. The influence of the photopolymer resin temperature on the surface defects appearance and deviations in geometric dimensions, as well as the layers exposure parameters influence on the photopolymer resin temperature, has been revealed. At the final stage of the study, it was found that the exposure parameters of the photopolymer model layers affect the photopolymer resin temperature, which, in turn, increases the likelihood of defects and geometric deviations in the finished model. Provided that the photopolymer resin temperature is kept within the range of 18–26°C, the model dimensions geometric deviation decreases by 0.054 mm along the XY axis and by 0.006 mm along the Z axis. A linear dependence of the size deviations on the exposure parameters and the photopolymer resin temperature has been established. The process of heat transfer from a UV radiation source to a photopolymer resin has been described. A thermodynamic scheme for controlling the resin temperature based on modeling the heat transfer between the exposed layers and the resin volume, considering the exposure time and UV radiation intensity, has been devised, which makes it possible to predict a critical temperature increase and minimize defects. While devising a method for controlling products during photopolymer 3D printing, the photopolymer temperature parameter was considered as one of the factors affecting the quality of parts and the level of rejects. Thus, the proposed method for controlling products during photopolymer 3D printing could be used to improve the technological process of manufacturing parts by reducing the number of defects and improving the finished products quality